BREAKFAST SKIPPING IS ASSOCIATED WITH INCREASED RISK OF TYPE 2 DIABETES AMONG ADULTS : A SYSTEMATIC REVIEW - Fitriana, Ilma; Intan Permatasari, Dela (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: While certain lifestyle habits may be associated with arterial stiffness, there is limited literature investigating the relationship between lifestyle habits and longitudinal changes in arterial stiffness in patients with type 2 diabetes mellitus (T2DM). Aims : This systematic review is to review the association of breakfast skipping and the risk of type 2 diabetes in adults. Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 569 articles, whereas the results of our search on SAGEPUB brought up 2731 articles, our search on SCIENCE DIRECT brought up 1382 articles. The results of the search conducted for the last year of 2014 yielded a total 335 articles for PubMed, 1173 articles for SAGEPUB and 864 articles for SCIENCE DIRECT. In the end, we compiled a total of 7 papers, 4 of which came from PubMed, 1 of which came from SAGEPUB and 2 of which came from SCIENCE DIRECT. We included seven research that met the criteria. Conclusion: In summary, breakfast skipping is associated in increasing of type 2 diabetes in adults but also need more studies because the studies of this topic is limited and less reported.